Methodical instructions for laboratory works on topic "Data modeling, building relational data structures in PostgreSQL and working with data using SQL" - Kopp, Andrii Mykhailovych; Orlovskyi, Dmytro Leonidovych; Ved, Olena Valeriivna; Vasylenko, Artem Viktorovych (Національний технічний університет "Харківський політехнічний інститут", 2025)
As part of the laboratory practicum, students acquire the knowledge and skills necessary for: - Building data models; - Selecting and applying database management systems (DBMS); - Designing, normalizing, and creating databases in relational DBMS using PostgreSQL as an example; - Working with relational DBMS using the Data Manipulation Language (DML) ofSQL (Structured Query Language). The goal of the laboratory practicum is to develop students' practical skills necessary for working with data models and structures in solving tasks related to the development, maintenance, and quality assurance ofsoftware.
Keywords: methodical instructions; laboratory works; data modeling; building relational data structures; PostgreSQL; SQL tools